Análise do processo de implantação de pesquisa online para levantamento de dados em saúde junto a universitários - Petersen, Cristina Buischi (2012)
University Health Promotion (UHP)is one that seeks continuous improvement of the factors that determine their physical and social environment through interventions that facilitate access and community resources that allow members to have autonomy with a view to mutual support. Objectives: To analyze the process of implementing a search for online questionnaires to survey health-related aspects of college; For this, was necessary: To analyze the instrument for a population similar to the target population; analyze the process of inclusion of research instruments that comprised the questionnaire on the platform of making online surveys (SurveyMonkey) analyze the feasibility of the method of research online, analyze the system records in databases generated by the program SurveyMonkey. Methods: The methodological approach was kind of survey design and descriptive analysis with quantitative and qualitative non probability samples or tests of hypotheses. The target population were 2011 students enrolled at a university in the state of Sao Paulo. Research instrument: questionnaire) ABEP.a1 Economy Class) Characterization of the general population: sex, age, etc.; b) screening test of involvement with alcohol, tobacco and other substances (ASSIST) c) Test Fargerström: Used to measure the nicotine addiction; d) Scale of Subjective Well-Being; e) Disorders Identification Test due to Alcohol - AUDIT f) WHOQOL BRIEF: An instrument for assessing quality of life developed by WHO; g) GHQ12 - General Health Questionnaire of Goldberg: h) Perceived stress Scale and other topics relevant to health. Results: The online questionnaire was effective for collecting and analyzing data. The insertion of the questionnaire in SurveyMonkey program is easy, quick, self-explanatory, intuitive. The online method of research in the university community proved to be feasible by the ease, convenience and comfort found that respondents, in addition to the virtual environment the natural environment where students live. Between days 03 and 17/11/2011 were invited 11,171 undergraduate students through a link on the site of the University. 1712 students agreed to participate (15.32%) answered the questionnaire altogether 1267 students (11.34%). The compliance rate was satisfactory for the short time that the questionnaire was made available on site. Some data were analyzed to demonstrate the efficiency and speed of the program SurveyMonkey to store and tabulate data, generating graphs instantly with layout options for the final presentation.Conclusion: The survey of health together online via the university indicates changes in the construction of knowledge, is a facilitator for getting data from the university community and enables the Institution of higher education goes beyond the field of scientific and technical information pointing to strategies that may guide educational actions aimed at promoting health in search of dynamic discussions that may allow integration of the university and the transformation of conventional university in University of Health Promotion. Keywords: Online research; universityhealth; school health; health education